Generalized models and the impacts of population density on COVID-19 transmission/ Modelos generalizados y los impactos de la densidad de población en la transmisión del COVID-19/ Modelos generalizados e os impactos da densidade populacional na transmissão da COVID-19 - Souza, Amaury de; Abreu, Marcel Carvalho; Oliveira-Júnior, José Francisco de; Alves Fernandes, Widinei; Aristone, Flávio; Martins de Souza, Debora; da Silva, Silvania Donato; Barros da Silva, Elania (Journal Health NPEPS, 2021)
Objective: to analyze epidemic curves based on mathematical models for the state of Mato Grosso do Sul and the impacts of population density on COVID-19 transmission. Method: the linear, polynomial and exponential regression model was used to make the numerical adjustment of the respective curves empirical. Result: it was found that the models used describe very well the empirical curves in which they were tested. In particular, the polynomial model is able to identify with reasonable reliability the appearance of the inflection point in the accumulated curves, which corresponds to the maximum point of the respective daily curves. The analysis indicates a weak positive correlation between infection, mortality, lethality and deaths from COVID-19 with population density, as revealed by the correlation and analysis of R2. Conclusion: the models are very effective in describing the COVID-19 and epidemic curves in the estimation of important epidemiological parameters, such as peak case curves and daily deaths, allowing practical and efficient monitoring of the evolution of the epidemic.